1999
DOI: 10.5488/cmp.2.4.685
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL AND ELECTRIC MANIFESTATIONS OF INCOMMENSURATE PHASE IN NH_{4}HSeO_{4} CRYSTALS

Abstract: Temperature dependences of the optical path difference by the variable part of refractive index D = (n − 1)l and the components ε ′ and ε ′′ of complex dielectric permittivity for NH 4 HSeO 4 single crystal are studied in the temperature range of 220-300 K. Anomalous behaviour of these dependences in the range of incommensurate phase 250-262 K was observed. Analysis of the results of dielectric investigation predicts a considerable decrease of the coefficient of elastic stiffness C in the narrow temperature ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The phase II is paraelectric monoclinic with space B2, and the phase III is an incommensurate. The NH 4 HSeO 4 crystal exhibits the ferroelectric phase IV in the temperature range between 98 and 250 K. The phase V below T C2 ¼ 98 K is nonferroelectric [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…The phase II is paraelectric monoclinic with space B2, and the phase III is an incommensurate. The NH 4 HSeO 4 crystal exhibits the ferroelectric phase IV in the temperature range between 98 and 250 K. The phase V below T C2 ¼ 98 K is nonferroelectric [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…The crystal then transits to the incommensurate phase (III) at 261 K (=T i ) and to the ferroelectric phase (IV) at 250 K (=T C1 ). When the temperature drops below 98 K (=T C2 ), the crystal commences its low temperature phase and becomes non-ferroelectric [12][13][14]. Previous studies of NH 4 HSeO 4 with 1 H nuclear magnetic resonance (NMR) spectra, nuclear spin-spin relaxation times T 2 , in the laboratory frame and conductivity measurements in the vicinity of T SI concluded that the diffusions of protons and NH 4 + cations in the crystals were isotropic [15,16].…”
Section: Introductionmentioning
confidence: 99%